2018
DOI: 10.3390/f9100599
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Participation in Natura 2000 Management Program: Case Study of Slovenia

Abstract: The Natura 2000 network, which is one of the largest networks of protected areas in the world, is the core pillar in the European Union’s biodiversity conservation policy. To achieve the national enforcement of Natura 2000 and to overcome implementation problems, effective policy measures are needed, and participation among different stakeholders is required. The aim of this paper was to evaluate the process of formulation of the Natura 2000 Management Program (2015–2020) in Slovenia based on a set of criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
(74 reference statements)
1
12
0
Order By: Relevance
“…Hence, the authors have examined (not randomly or systematically, but through a snowball sampling technique) stakeholders' perceptions concerning their participation in the making of MPs, while this work has proposed a systematic assessment of official documents that have recorded such participation. Therefore, further research could bridge the two assessments and combine a systematic survey of stakeholders who took part (in whichever form) in SAC designation processes with the documental analysis here presented, so as to compare stakeholders' perceptions (on which focus, for instance, [31] and [64]), with the official narrative, hence ultimately assessing participation effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the authors have examined (not randomly or systematically, but through a snowball sampling technique) stakeholders' perceptions concerning their participation in the making of MPs, while this work has proposed a systematic assessment of official documents that have recorded such participation. Therefore, further research could bridge the two assessments and combine a systematic survey of stakeholders who took part (in whichever form) in SAC designation processes with the documental analysis here presented, so as to compare stakeholders' perceptions (on which focus, for instance, [31] and [64]), with the official narrative, hence ultimately assessing participation effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The voluntary character envisioned in the directive notwithstanding, ad-hoc plan-making processes (i.e., the definition of management plans containing the required conservation measures) are regarded in several studies as the way forward to mitigate conflicts [26,27] and as the optimal tool to include stakeholders' participation [16,[28][29][30]; management plans have therefore been found to be preferred over stand-alone conservation measures in a number of member states and have been promoted by the EU [25]. Moreover, inclusive plan-making processes are regarded in the literature as a proper counterbalance to the top-down process whereby Natura 2000 sites were identified and designated [31].…”
mentioning
confidence: 99%
“…Stakeholder participation, cooperation, and their ability to influence the policy decision-making process are, as identified in numerous studies (e.g., [8,[40][41][42]52]), the key factors for policy implementation success.…”
Section: Social Factorsmentioning
confidence: 99%
“…Many previous studies have shown that national implementation of nature conservation policies differs across the EU [7][8][9][22][23][24][25]. Differences in implementation pathways are related to differences in policy culture in each country and consequently policy integration [14,[26][27][28][29], financing of conservation measures and compensation payments [29][30][31][32][33], management practices [34,35], institutional factors [3,13,23,29,[36][37][38], social factors [3,15,[39][40][41][42][43][44][45], and environmental factors [46,47]. In a recent review of studies related to nature conservation, Popescu, et al [48], and Blicharska, Orlikowska, Roberge and Grodzinska-Jurczak [21], concluded that research related to ecological factors prevail, while social, economic, and policy ones are underrepresented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation